2022
DOI: 10.1002/aenm.202202097
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Heterogeneous Catalysts under Reaction Conditions by In Situ/Operando Electron Microscopy

Abstract: The advancement of clean energy and environment depends strongly on the development of efficient catalysts in a wide range of heterogeneous catalytic reactions, which has benefited from transmission electron microscopic techniques in determining the atomic‐scale morphologies and structures. However, it is the morphology and structure under the catalytic reaction conditions that determine the performance of the catalyst, which has captured a surge of interest in developing and applying in situ/operando transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 290 publications
0
12
0
Order By: Relevance
“…A TEM equipped with an energy dispersive spectrometer (EDS) can analyze the elemental composition of the sample. 131 With the development of ambient TEM, it has been demonstrated that the dynamic morphology change can be captured in solid or gas phases, even at the solid-liquid interface. Using MEMS technique, Wang et al 46 fabricated a gas cell for real-time observation of the microscopic morphology of ZnO nanowires in the reaction with SO 2 (1 bar).…”
Section: In Situ Experimentsmentioning
confidence: 99%
“…A TEM equipped with an energy dispersive spectrometer (EDS) can analyze the elemental composition of the sample. 131 With the development of ambient TEM, it has been demonstrated that the dynamic morphology change can be captured in solid or gas phases, even at the solid-liquid interface. Using MEMS technique, Wang et al 46 fabricated a gas cell for real-time observation of the microscopic morphology of ZnO nanowires in the reaction with SO 2 (1 bar).…”
Section: In Situ Experimentsmentioning
confidence: 99%
“…This nanobattery worked only for a few cycles, which was unencapsulated, hindering the study of structural evolutions in real batteries. [77,78] Some researchers also revealed the nanoparticle growth and coalescence in ionic liquids at atomic resolution by the open cells. [79,80] They also faced the issue that the ionic liquid electrolyte might polymerize, so chemical reactions were insufficient.…”
Section: Open Liquid Cellsmentioning
confidence: 99%
“…[28] There are also a few recent reviews involving different aspects of in situ TEM relating to catalysis and energy conversion. [4,10,[29][30][31][32][33][34][35][36] The nanocrystal's structure and property play a central role in the above aspects but their dynamics under working conditions need to be further contemplated. It is a perfect time to review progress on the dynamic insights into nanocrystals and propose future directions for further investigations.…”
Section: Brief Introduction Of In Situ Transmission Electron Microscopymentioning
confidence: 99%